种茚并吡唑类小分子微管蛋白抑制剂及其制备方法与应用 (2017)
本发明公开了种茚并吡唑类小分子微管蛋白抑制剂，其特征在于，具有通式I所示的结构：其中，R代表NH或NHOH；本发明还公开了该茚并吡唑类化合物或其药用盐的制备方法。本发明的化合物为结构新颖的茚并吡唑类小分子微管蛋白抑制剂，对人肝癌HepG2细胞、人前列腺癌PC3细胞，人子宫颈癌HeLa细胞，人乳腺癌MCF-7细胞和人白血病K562细胞有很强的增值抑制活性，作用机制与秋水仙碱相似，能够抑制微管蛋白聚合，对于增强药物的特异性、有效性，减少毒副作用和防止耐药性等都有很重要的意义。 The invention discloses an indeno pyrazole micromolecular tubulin inhibitor which is characterized by comprising a structure which is shown in a general formula I, wherein R represents NH2 or NHOH. The invention further discloses a preparation method of an indeno pyrazole compound or officinal salt of the indeno pyrazole compound. The compound disclosed by the invention is the indeno pyrazole micromolecular tubulin inhibitor which is novel in structure, and has strong proliferation inhibition activity to a human liver cancer HepG2 cell, a human prostatic cancer PC3 cell, a human cervical carcinoma HeLa cell, a human breast cancer MCF-7 cell and a human leukemia K562 cell. The mechanism of action of the compound is similar to that of colchicine. Tubulin polymerization can be